Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s10086-007-0893-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of board density and layer structure on the mechanical properties of bamboo oriented strandboard

Abstract: This study examined the effect of density and layer structure on the mechanical properties and dimensional stability of strandboard manufactured from moso bamboo (Phyllostachys pubescens). The strandboard was fabricated in a laboratory at five densities and three different structures including a randomly oriented homogenous board, a unidirectionally oriented homogenous board, and a three-layered board with a cross-oriented core layer (BOSB). Bamboo strand alignment distribution could be predicted using the von… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 6 publications
1
34
0
2
Order By: Relevance
“…According to Ismardi et al [13], the factors affecting the MOR value were density of wood particle board, particle geometry, particle orientation, grade adhesive resin content, moisture content, pressing condition, and procedures. MOR value results for boards in parallel position were: type A (157.3 kgf/cm²), type B (156.6 kgf/cm²), and type C (47.8 kgf/cm²).…”
Section: Modulus Of Elasticity and Modulus Of Rupturementioning
confidence: 99%
“…According to Ismardi et al [13], the factors affecting the MOR value were density of wood particle board, particle geometry, particle orientation, grade adhesive resin content, moisture content, pressing condition, and procedures. MOR value results for boards in parallel position were: type A (157.3 kgf/cm²), type B (156.6 kgf/cm²), and type C (47.8 kgf/cm²).…”
Section: Modulus Of Elasticity and Modulus Of Rupturementioning
confidence: 99%
“…(Hermawan et al 2007), bamboo (Sumardi et al 2007;Cheng et al 2012), mixing several types of wood chips (Zhang et al 1998), or using wood from fireimpacted trees (Moya et al 2009). It has also been shown that using fine chips as a core layer component does not cause any significant deterioration of board properties (Fakhri et al 2006a;Fakhri et al 2006b;Han et al 2006;Han et al 2007;Mirski and Dziurka 2011a;Mirski and Dziurka 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Density is a physical parameter that significantly affects the physical and mechanical properties of wood-based materials, particularly the modulus of rigidity and modulus of elasticity (Sumardi et al 2007;Grandmont et al 2010), and reduction in the density decreases these properties. However, literature indicates that currently-produced OSBs are characterized by much better properties, mainly mechanical, than required by EN standard 300 (Dziurka et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the removal of the outer and inner skin is an indispensable process for producing these products, which results in better bonding performance between resin and materials. In addition, a huge amount of planing waste (more than 65%) has been obtained during bamboo strip preparation for panel development (Zhang et al 2013;Sumardi et al 2007;Pannipa et al 2011). Many attempts have been undertaken to improve the utilization ratio of bamboo through reconstituting bamboo (Li et al 2007;Nugroho and Ando 2000;2001;Mhmad and Kamke 2005;, but the production of high-performance bamboobased panel is still impracticable due to the high resin addition and the free formaldehyde emission levels, and high capital requirements for facilities.…”
Section: Introductionmentioning
confidence: 99%
“…"Corrugated bamboo particleboard," BioResources 9(1), 1085-1096. 1087 2004; Zhang et al 2013;Sumardi et al 2007). Furthermore, its fast growth rate can support intensive and sustainable use in the particleboard industry (Mahdavi et al 2012;Umit et al 2012).…”
Section: Introductionmentioning
confidence: 99%